Plan de negocios para la creación de una guardería con atención al público de 14 horas con énfasis en el cuidado de los niños en la localidad de Kennedy de la ciudad de Bogotá - Olivares Álvarez, Daniel Eduardo (Universidad Antonio Nariño, 2021)
The purpose of this project is to create a care and learning nursery for children between 1 and 4 years old, this nursery would be legally registered with the name of La Abejita de Colores, which would be located in the Eighth Kennedy Town in the city. of Bogotá, providing a service to the neighborhoods El Olivo, Villa Nelly, Villa Latorre and firemen, guaranteeing a service of 14 hours, which will facilitate the care of children, in which both parents are working or studying